Going for Gold: New Zealand houses in the 60s through the veil of the NZIA Bronze Medals - McCarthy, Christine (Architectural History Aotearoa, 2024)
In 1926 the New Zealand Institute of Architects instituted a Gold, Silver, Bronze Medal system to recognise its members’ work. By the 1960s, the Bronze Medal recognised the best designed single-unit house. The award system appears to have been a strict one, the Institute feeling no obligation to award the Bronze Medal in 1962, 1964 and 1969. This paper looks at the seven houses recognised by the Bronze Award in the 1960s.